Determinants of Financial Statement Fraud: An Analysis Based on the Fraud Star Theory - Qintharah, Yuha Nadhirah; Octaviani, Gita (JABE (JOURNAL OF ACCOUNTING AND BUSINESS EDUCATION), 2026)
A number of previous empirical studies have attempted to reveal the existence of This study aims to analyse the elements of the fraud star that can affect the occurrence of financial statement fraud in Consumer Non-Cyclicals sector companies listed on the Indonesia Stock Exchange (IDX). There are 213 samples from 71 companies in the Consumer Non-Cyclicals sector listed on the Indonesia Stock Exchange for the 2021-2023 period. Hypothesis testing is carried out through panel data regression analysis using EViews 12 to test the influence between the dependent variable and the independent variable. Based on the results of partial testing that has been carried out, this study shows that the financial target variable and Ineffective monitoring have no effect on financial statement fraud. Change in auditor, change in director and integrity have a negative effect on financial statement fraud. Meanwhile, financial stability has a positive effect on financial statement fraud. So, with this, it is hoped that future researchers can use different fraud theories and use other dependent variables such as asset misuse or corruption.